An Exploratory Study on How Democratic School Management Practices Affect the Dynamics of Violence in Schools - van der Merwe, Petro (International Journal of Criminology and Sociology, 2016)
The goal of teachers, schools and support staff is the optimal development of learners. This goal depends on effective school management, which in turn depends on an adequate curriculum and supporting teaching and learning environments. This paper is focused through a literature review on the dynamics of violence in South African schools and the need for democratic school management. The necessity of emotional intelligence teaching in the classroom and learner-centred teaching is shown. This study also investigated the coordinated and integrated management of positive learner behaviour, whole school development and management of a culture of positive behaviour. The establishment of a safe school depends on the management's interaction with the larger social and organisational context in which they find themselves. The study concludes that there is a correlation between Emotional Intelligence teaching methods and learners' behaviour. The use of Emotional Intelligence in the classroom can be regarded as the corrective aspect of discipline, thus, preventing inappropriate behaviour of learners. Recommendations and guidelines for the use of effective adjusted and alternative teaching methods to support school management in the use of emotional skills in the school context are provided.